VEGETATION DEVELOPMENT ANALYSIS IN GRASBERG AREA PT FREEPORT INDONESIA (PTFI)AFTER 20 YEARS RECLAMATION - Firman Firdaus, Muhammad
In order to restore environmental conditions damaged by mining activities, PT Freeport Indonesia has done reclamation activities for approximately 20 years in Grasberg area. Grasberg area, which divided into two zones, zone alpine (> 4000 masl) and subalpine (2400-4000 masl) and has extrem climatic conditions. The temperature ranges from 8-22oC and can even reach freezing points (-2oC to -5oC) with high rainfall (7000 mm/year). This condition cause only few species of flora and fauna can survive. Reclamation activities in Grasberg, produce vegetation with various sites age. This condition is possible to do a vegetation development study using chronosequence approach. The purpose of this reseach to examine development of vegetation using the chronosequence approach in Grasberg PTFI reclamation area and to compare vegetation development patterns of vegetation formed between alpine and subalpine zones. This study uses secondary data that contain vegetation observation data in the Grasberg reclamation area from 2016-2019 including seven alpine reclamation sites (age 7, 8, 10 16, and 17 years), two alpine reference sites, six subalpine reclamation sites (age 6, 7, 8, 9, 10, and 20 years), and two subalpin reference sites. Vegetation data comes from observation on 332 plots with 3x3 m2 plot. The data were analyed using biodiversity parameter and multivariat analysis ordination NMDS (Non-Metric Multidimensional Scaling) and ANOSIM test using PRIMER software. The analysis is used to examine of development vegetation formed. In Grasberg area, the composition of the vegetation was found such as 53 species from 23 families. Asteraceae is the most common family. The forms/levels of life found include moss, ferns, fungi, herbs, shrubs, and seedlings with herbaceous life forms dominating as much as 63%. Diversity in the alpine zone increased with increasing site age, but in the subalpine zone decreased at site (age 7, 8, 9, and 10 years). Deschampsia klossii (herbaceous) species dominated in all sites, except for the six years old site (subalpin) which was dominated by Bryum sp (moss). The results of multivariate analysis: NMDS (Non-Metric Multidimensional Scaling) ordination in the Grasberg reclamation area of the alpine and subalpine zones showed different patterns of vegetation development. ANOSIM test showed patterns development vegetation between alpin zone and subalpine not significant.